2006
DOI: 10.1111/j.1365-2591.2006.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 production and viability of cells cultured in contact with freshly mixed endodontic materials

Abstract: Under 24-h culture conditions, the three freshly mixed test materials did not increase directly either production or release of PGE2 from either macrophages or gingival fibroblasts. Roth 801 decreased cell viability counts for both fibroblasts and macrophages. Sealapex decreases macrophage viability. ProRoot MTA did not affect viability in either cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…2, the expression of iNOS was increased at 3 hours. Moreover, PGE 2 was increased at about 3 hours, and the levels continuously increased thereafter (Fig.1B), whereas previous study demonstrated that MTA did not stimulate PGE 2 release from macrophages (29). These differences might be due to cell specificities.…”
Section: Discussionmentioning
confidence: 57%
“…2, the expression of iNOS was increased at 3 hours. Moreover, PGE 2 was increased at about 3 hours, and the levels continuously increased thereafter (Fig.1B), whereas previous study demonstrated that MTA did not stimulate PGE 2 release from macrophages (29). These differences might be due to cell specificities.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, stimulation with IL-1b has been shown to induce RANKL and OPG expression, with high IL-1b levels leading to a significant increase in RANKL expression in primary human cementoblasts (24). Products of the arachidonic acid pathway, most noticeably PGE2, are the principal mediators of inflammatory pain (25). Also PGE2 can induce osteoclast formation from RAW 264.7 cells cocultured with mouse osteoblasts (26).…”
Section: Discussionmentioning
confidence: 99%
“…Another investigation compared WMTA, Sealapex, and Roth 801 on macrophages and gingival fibroblasts (153). Only WMTA showed no adverse effect on the viability of either cell line, and none of the materials tested increased the release of prostaglandin E 2 (PGE 2 ).…”
Section: Cell Culturesmentioning
confidence: 99%